ANALISIS PENGARUH PRODUK GADAI EMAS (RAHN EMAS) TERHADAP PENINGKATAN FEE BASED INCOME (FBI) PADA PT. BANK SYARIAH MANDIRI - Ismaulina Ismaulina; Oumar Tidiane Doumbouya (Imara: JURNAL RISET EKONOMI ISLAM, 2020)
Fee Based Income is the income that keeps the company from decreasing the net interest margin (NIM). The amount of profit obtained by the bank as well as being efficient and effective in managing company finances, shows a good bank financial performance. One of the products of PT. BSM that provides Fee Based Income is Gold Pawn (rahn) services provided by banks to customers. This research uses quantitative data. Data obtained from the monthly financial statements of gold pawn products and FBI at PT. Bank Syariah Mandiri period January 2017 - December 2019. This study uses a simple linear regression method. Regression analysis shows that the effect of gold rahn on fee based income is significant where t count (3.826)> t table (2.03) and a significance of 0.001 <0.05 so that Ho is rejected and Ha is accepted. It can be concluded that the Gold Rahn variable has a significant effect on FBI. This happens because the total gold Rahn fee received by Bank Syariah Mandiri makes a significant contribution to the bank's profit rate.